INNOVATION STRATEGY TO ACHIEVE COMPETITIVE ADVANTAGE IN HOTEL KUSUMA AGROWISATA BATU - Try Noviyanti; Desi Tri Kurniawati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This study aims to analyze whether the innovation strategy at Hotel Kusuma Agrowisata Batu can create competitive advantage. The method used in this research is qualitative research. Data obtained by interview to the management of Hotel Kusuma Agrowisata Batu (Internal) and via the internet, books, articles (external), while the data collection method is case study. Analysis tools used include analysis of EFAS, IFAS Analysis, SWOT Analysis, and Analysis of Grand Strategy. IFAS and EFAS Analysis results showed that the total value of the power is greater than the total value of total weakness and opportunity greater than the total threat. In the SWOT analysis matrix generated alternative strategies SO Grand Strategy and the analysis shows Kusuma Agrowisata Batu Hotel occupies the first quadrant position which means an aggressive position. Results of the analysis showed that the innovation strategies undertaken by Hotel Kusuma Agrowisata Batu is product innovation strategy and managerial innovation. Thus it can be said that a business accommodates Kusuma Agrowisata Batu hospitality services to achieve competitive advantage.Keywords: Strategi Agresif, Strategi Inovasi, Strategi Generik, IFAS, EFAS, Matriks SWOT, Grand Strategy